2016
DOI: 10.4137/ccrep.s40420
|View full text |Cite
|
Sign up to set email alerts
|

Primary Metastatic Squamous Cell Carcinoma of the Male Urethra Presenting with Scrotal Abscess and Subsequent Development of Fournier's Gangrene

Abstract: This male patient presented with a scrotal abscess and urinary obstruction. The patient’s history included a perineal abscess and the development of urethrocutaneous fistulae (watering-can perineum). He underwent multiple debridement procedures without resolution. During the fifth debridement for Fournier’s gangrene, a biopsy revealed invasive squamous cell carcinoma. The patient was bedridden because of the large mass, a wide en bloc resection with lymphadenectomy and reconstruction was performed revealing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Local procedures and chronic indwelling catheters increase the risk of infection. Chemotherapy as a treatment for a previously diagnosed unrelated cancer was seen in 15% (3/20) of the case reports [3][4][5][6][7].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Local procedures and chronic indwelling catheters increase the risk of infection. Chemotherapy as a treatment for a previously diagnosed unrelated cancer was seen in 15% (3/20) of the case reports [3][4][5][6][7].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…It is included in many medical calculator applications and includes the measurement of CRP, hemoglobin, white blood cell count, serum sodium, creatinine, and blood glucose level. Scores of ≥6 raise the suspicion for necrotizing fasciitis/FG and scores of ≥8 are strongly predictive of the disease [5,17]. Initial studies of the LRINEC score showed a 92% positive predictive value in diagnosing FG but subsequent studies have questioned its utility [19].…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations